Pengaruh Ekspor Komoditas Utama terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan - Nahda Muzlena; Syahrituah Siregar (PPJP Universitas Lambung Mangkurat, 2020)
This research analyzed the export of primary commodities on labor absorption in the South Kalimantan Province. The amount of data used is 15 years, which can be used in the data processing. Data is processed using panel data regression analysis. The results are finding that the effect export of primary commodities has a significant effect on labor absorption.